School Financing Analysis To Improve The Quality of Education In SMP and SMA Babul Maghfirah Aceh Besar - Irfan, Muhammad; Usman, Nasir; Bahrun, Bahrun (Pelopor Publikasi Akademika, 2024)
Education is a process in developing one's own abilities and individual strengths. According to the Indonesian Dictionary, education is a process of changing the attitude and behavior of a person or group of people in an effort to mature human beings through teaching and training efforts. This study aims to analyze financing management in Babul Maghfirah Junior and Senior High School, Aceh Besar, as well as its implications for improving the quality of education. Using a qualitative approach and descriptive methods, this study explores the process of preparing School Activity Plans and Budgets (RKAS), the implementation of financing, as well as the challenges and supporting factors in school financing. The results of the study show that effective, transparent, and accountable financing management plays an important role in improving the quality of education in schools. In addition, the support from the government, parents, and school committees greatly determines the success of fund management and its allocation. This study recommends increasing cooperation between stakeholders in the management of education funds as well as improvements in the budgeting process to suit the real needs of schools.